2016
DOI: 10.1007/s11120-016-0224-3
|View full text |Cite
|
Sign up to set email alerts
|

Towards efficient photosynthesis: overexpression of Zea mays phosphoenolpyruvate carboxylase in Arabidopsis thaliana

Abstract: Plants with C4 photosynthesis are efficient in carbon assimilation and have an advantage over C3 photosynthesis. In C4 photosynthesis, the primary CO fixation is catalyzed by phosphoenolpyruvate carboxylase (PEPC). Here, we show that overexpression of Zea mays PEPC cDNA, under the control of S promoter, in Arabidopsis thaliana resulted in ~7-10 fold higher protein abundance and ~7-10 fold increase in PEPC activity in the transgenic lines than that in the vector control. We suggest that overexpression of PEPC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 125 publications
4
27
0
Order By: Relevance
“…Similarly, transgenic tobacco plants expressing a bifunctional cyanobacterial fructose-1,6 /sedoheptulose-1,7-bisphosphatase in chloroplasts had higher photosynthesis and dry matter production (Miyagawa et al, 2001 ). In our laboratory, Kandoi et al have previously shown that the overexpression of maize phosphoenolpyruvate carboxylase (PEPC) in A. thaliana resulted in increased photosynthesis and biomass (Kandoi et al, 2016 ). PEPC in C4 carbon metabolism also plays a crucial role in the nitrogen assimilation (Shi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transgenic tobacco plants expressing a bifunctional cyanobacterial fructose-1,6 /sedoheptulose-1,7-bisphosphatase in chloroplasts had higher photosynthesis and dry matter production (Miyagawa et al, 2001 ). In our laboratory, Kandoi et al have previously shown that the overexpression of maize phosphoenolpyruvate carboxylase (PEPC) in A. thaliana resulted in increased photosynthesis and biomass (Kandoi et al, 2016 ). PEPC in C4 carbon metabolism also plays a crucial role in the nitrogen assimilation (Shi et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that in C 3 cereals the enzyme NADH-GOGAT is important for yield performance (Tamura et al, 2011). The C 4 photosynthetic pathway is considered a key biotechnological target for crop improvement (Covshoff and Hibberd, 2012;Kandoi et al 2016).…”
Section: Predictive Value Of Physiological Markers For Yield and Its mentioning
confidence: 99%
“…This might suggest a role for PPC3 in the synthesis of proline and thus in the response of the plant to salt stress. Transgenic Arabidopsis plants overexpressing C 4 PEPC from Zea mays were more tolerant to salt stress due to an increased ability to synthesize amino acids, including proline (Kandoi et al 2016). On the other hand, we previously found that raised PEPC activity in Fe-deficient and/or salt-stressed barley leaves was not directly responsible for supplying C for proline synthesis (AriasBaldrich et al 2015).…”
Section: Discussionmentioning
confidence: 99%